Effect of Brain Damages on Logical Inferences of Depressive Adults - Javeria Sajid; Muhammad Naveed Riaz (Journal of the Pakistan Medical Association, 2022)
Objective: To examine the immediate and mediate inferences among depressive adults with and without brain damage. Methods: The descriptive, comparative study was conducted from November 6 to June 19, 2019, in Sargodha, Pakistan, and comprised depressive adults of either gender enrolled from various local mental health facilities. After applying Stroop test to identify brain damage, the subjects were divided into adults with brain damage in group A, and adults without brain damage in group B. Logical inferences of both groups were identified using three decision situations, and the findings were compared between the groups. Results: Of the 170 individuals approached, 120(70.5%) were included; 60(50%) in each of the two groups. Overall, there were 76(63%) males and 44(37%) females. The overall age range 18-60 years, with 105(88%) being young adults aged 18-49 years. Chi-Square Test was applied to test the hypotheses. Findings revealed that Group A exhibited higher frequency of immediate inferences on three conditions of certainty (55, 53, 58) as compared to Group B (23, 21, 20) while group B exhibited higher frequency on mediate inferences on the conditions of certainty (37, 39, 40) as compared to Group A (5, 7, 2). Group A exhibited higher frequency of immediate inferences on three conditions of risk (54, 55, 56) as compared to Group B (14, 23, 22) ----Continue